2016
DOI: 10.1109/mcg.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Sculpting and 3D Printing for Young People with Disabilities

Abstract: Abstract:In this paper, we present the SHIVA project which was designed to provide virtual sculpting tools for young people with complex disabilities, to allow them to engage with artistic and creative activities that they might otherwise never be able to access. Modern 3D printing then allows us to physically build their creations. To achieve this, we combined our expertise in education, accessible technology, user interfaces and geometric modelling. We built a generic accessible graphical user interface (GUI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
0
6
0
10
Order By: Relevance
“…Additive manufacturing allows automatic fabrication of products of complex shape with a significant reduction in manufacturing cost, compared to traditional subtractive manufacturing techniques [1,2]. In the last decade, the application of additive manufacturing has grown substantially in both volume and scope [3][4][5], mainly due to the availability of relatively inexpensive 3D-printing devices. Additive manufacturing techniques available commercially include stereolithography (STL), selective laser sintering (SLS), inkjet printing (IP) and fused deposition modelling (FDM) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing allows automatic fabrication of products of complex shape with a significant reduction in manufacturing cost, compared to traditional subtractive manufacturing techniques [1,2]. In the last decade, the application of additive manufacturing has grown substantially in both volume and scope [3][4][5], mainly due to the availability of relatively inexpensive 3D-printing devices. Additive manufacturing techniques available commercially include stereolithography (STL), selective laser sintering (SLS), inkjet printing (IP) and fused deposition modelling (FDM) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Common themes of motivation have emerged including activities involving 'fun', control (especially physical control), creativity (McLoughlin et al, 2016) and those where there is an element of challenge or competition. The control of simple toys and more advanced robotic toys has been found to be very engaging.…”
Section: System Design Methodsmentioning
confidence: 99%
“…Accessibility is an essential point of focus; each individual has specific needs and abilities and so the user interface and hardware need to be adaptable to suit each person, through customisation and, sometimes, bespoke solutions. An example of this is The Shiva Project (McLoughlin et al, 2016) which identified the importance of a flexible profile-based user interface when creating systems for a range of individuals who have special requirements.…”
Section: System Design Methodsmentioning
confidence: 99%
“…De acuerdo al origen de la investigación, la Figura 6A no reporta aportes de países latinoamericanos y africanos, con excepción de México. La mayoría proviene de países europeos (52 %) (Giraud, 2017;Mcloughlin, 2016;Bonnet de León, 2020;Evelyn-Wright et al, 2020;Molins-Ruano, 2018;Clements, 2016;Díaz-Navarro & Sánchez de La Parra-Pérez, 2021;Götzelmann, 2018;Gual-Orti, 2015;Koelemeijer & Winterbourne, 2021;Kostakis et al, 2015). Las publicaciones restantes se distribuyen entre Norteamérica, con 29 % (Hernández Sánchez, 2020;Smith, 2020;Grumman & Carroll, 2019;Wedler, 2012;Buehler, 2016;VanderMolen & Fortuna, 2021;LeSuer, 2019), y Asia, con 19 % (Jain, 2018;Singhal & Balaji, 2020;Wu, 202;See, 2021).…”
Section: Adhesión De Los Artículos a Los Pilares De La Instrucción Ex...unclassified